Public Relations in Tourism - Nargiza Akbarjonovna Abduvakhidova; Takhmina Kamiljonovna Akramova (Indonesian Journal of Law and Economics Review, 2020)
Nowadays the topic of public relations is being actively promoted in literature and press. It is obvious that, it has become clear that this is an important part of our daily bases. It deals with the sphere of management, especially with the issue concerned Uzbekistan. Sometimes countries are constantly exposed to various crises with serious consequences. To balance these effects, the management and public relations have been applied. So that that a great deal of attention is paid to political PR. As for political PR, the ability of public relations to manage crises, to relieve tension, to ease the situation, to reset public attitudes, to regain people's approval and trust in the activities of the authorities is also widely used in the spectrum of its debate. Important to note that, the business sector has been studied less than it should be. Traditional aspects of the research are election campaigns, work for the prestige of politicians, and in the commercial area, banks and some large companies. We should take into consideration that small and medium business as it is in this domain that lies the basis of development for our country. Besides, it seems to me that although public relations in small companies do not have this scale, they are very important for healthy development. Therefore, it is necessary to explore and develop methods of public relations for the private business sphere.